2020
DOI: 10.3390/toxins12090578
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using New Synbiotics on the Turkey Performance, the Intestinal Microbiota and the Fecal Enzymes Activity in Turkeys Fed Ochratoxin A Contaminated Feed

Abstract: The feed supplementation of probiotic microorganisms is a promising method for detoxification of ochratoxin A (OTA) in poultry. The aim of the study was to investigate the effect of newly elaborated synbiotics on the turkey performance, the intestinal microbiota and its enzymatic activity in turkeys (0–15 weeks) fed OTA contaminated feed (198.6–462.0 µg/kg) compared to control group (OTA-free feed). The studies determined the composition of intestinal microorganisms by the culture method and the activity of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
(69 reference statements)
2
17
0
Order By: Relevance
“…The properties of probiotic strains and prebiotic included in the developed synbiotics have been tested according to the procedures recommended by EFSA and FAO/WHO 14,21 . Furthermore, the effectiveness of the synbiotics in breeding of monogastric animals (poultry and piglets) has been studied so far in many in vivo and in vitro research studies 6‐9,22,23 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of probiotic strains and prebiotic included in the developed synbiotics have been tested according to the procedures recommended by EFSA and FAO/WHO 14,21 . Furthermore, the effectiveness of the synbiotics in breeding of monogastric animals (poultry and piglets) has been studied so far in many in vivo and in vitro research studies 6‐9,22,23 …”
Section: Methodsmentioning
confidence: 99%
“…The content of basic nutrients in the mixtures was determined according to the principles of the Weenden method (AOAC 2005). The nutritional value and composition of the turkey feed mixtures were the same as the negative control group of animals and are detailed in our other article 8 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were confirmed by Zhai et al, who further demonstrated that OTA also alters the metabolism of intestinal microbiota in ducks [ 33 ]. Changes in the diversity and in the composition of gut microbiota caused by OTA have also been found in OTA-fed broilers [ 34 ] and turkeys [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al, 2017). These complex interactions between the gastrointestinal microbiota, host, and mycotoxins also significantly influence how the mycotoxicosis will develop further (Hermann-Bank, Skovgaard, Stockmarr, Larsen, & Mølbak, 2013;Śliżewska, Markowiak-Kopeć, Sip, Lipiński, & Mazur-Kuśnirek, 2020).…”
Section: Introductionmentioning
confidence: 99%